Call for papers for the issue 4-2022 (Vojnotehnički glasnik / Military Technical Courier, 2022)
The instructions to authors about the article preparation for publication in the Military Technical Courier are based on the Regulations on categorization and ranking of scientific journals of the Ministry of Education, Science and Technological Development of the Republic of Serbia (Official Gazette of the Republic of Serbia, No 159/20). This Regulations aims at improving the quality of national journals and raising the level of their compliance with the international system of scientific information exchange. The editorial policy of the Military Technical Courier is based on the COPE Core Practices, common COPE, DOAJ, OASPA and WAME Principles of Transparency and Best Practice in Scholarly Publishing as well as on the best accepted practices in scientific publishing. The Military Technical Courier has been a COPE (Committee on Publication Ethics) member since 2nd May 2018 and a member of OASPA (Open Access Scholarly Publishers Association) since 27th November 2015.
Keywords: Vojnotehnički glasnik; Military Technical Courier; call for papers; instructions for authors